2019
DOI: 10.1253/circj.cj-19-0352
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Soluble Epoxide Hydrolase in Macrophages Ameliorates the Formation of Foam Cells ― Role of Heme Oxygenase-1 ―

Abstract: Background: Accumulation of foam cells in the neointima represents an early stage of atherosclerosis. 1-trifluoromethoxyphenyl-3-(1-propionylpiperidine-4-yl) urea (TPPU), a novel soluble epoxide hydrolase inhibitor (sEHi), effectively elevates epoxyeicosatrienoic acid (EET) levels. The effects of EETs on macrophages foam cells formation are poorly understood. Methods and Results: Incubation of foam cells with TPPU markedly ameliorate cholesterol deposition in oxidized low-density lipoprotein (oxLDL)-loaded mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
(30 reference statements)
0
4
0
Order By: Relevance
“… 314 The elevated DHET could indirectly imply elevated sEH activity or expression and pretreatment with sEH inhibitors has been reported to significantly improved the stability of EETs in various types of biological samples. 315 , 316 Since these early reports the development of methodology, especially ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLCMS/MS) has made EET analyses more specific and sensitive. 317 , 318 Using such techniques, EETs have been detected in tumor tissues or cells in various conditions.…”
Section: Aa Metabolisms In Cancermentioning
confidence: 99%
“… 314 The elevated DHET could indirectly imply elevated sEH activity or expression and pretreatment with sEH inhibitors has been reported to significantly improved the stability of EETs in various types of biological samples. 315 , 316 Since these early reports the development of methodology, especially ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLCMS/MS) has made EET analyses more specific and sensitive. 317 , 318 Using such techniques, EETs have been detected in tumor tissues or cells in various conditions.…”
Section: Aa Metabolisms In Cancermentioning
confidence: 99%
“…In bone marrow-derived macrophages (BMDM), application of AUDA, an inhibitor of sEH-H activity, did not affect macrophage intracellular cholesterol accumulation, and application of ebselen, an inhibitor of sEH-P activity, exacerbated macrophage intracellular cholesterol accumulation, suggesting that sEH-H is not involved in BMDM cholesterol metabolism, whereas sEH-P decreased intracellular cholesterol levels ( Lien et al, 2019 ). In THP-1, sEH-H and sEH-P act together to attenuate intracellular cholesterol accumulation in macrophages ( Lien et al, 2019 ; Peng et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature reported that in THP-1 haem oxygenase-1 (HO-1) inhibits transcription factor AP-1-mediated SR-A expression and decreases calpain protease activity to increase ABCA1 stability ( Tsai et al, 2010 ). TPPU inhibits the EH activity of sEH, stabilizes EETs, enhances the role of EETs in promoting HO-1 expression, and finally inhibits the formation of foam cells through HO-1 mediated cholesterol regulation ( Peng et al, 2019 ). Vascular smooth muscle cells can also form foam cells by uptake of cholesterol ( Allahverdian et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The tight association between EPHX2 and ox-LDL was also highlighted in another animal study, where blocking of soluble EPHX2 was accompanied by a rise in β -oxidation of fatty acids [ 36 ]. In vitro, incubation of foam cells with a novel inhibitor of soluble EPHX2 caused a significant decrease in cholesterol accumulation in ox-LDL-loaded macrophages [ 37 ], possibly by increasing the circulating epoxyeicosatrienoic fatty acids. Inhibition of soluble EPHX2 promoted cholesterol efflux and prevented the internalization of ox-LDL cholesterol.…”
Section: Discussionmentioning
confidence: 99%